2012
DOI: 10.4236/ojss.2012.21008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic and Inorganic Amendments on the Phytoavailability of Phosphorus to Corn (<i>Zea mays</i>)

Abstract: A pot experiment was conducted to investigate the effect of cow manure, city waste, chicken manure and TSP on the growth of corn (Zea mays) and phytoavailability of phosphorous (P) in soil. An air dried sandy loam soil was mixed with different amendments at rates equivalent to 0, 200, 400 and 800 mg·P·kg -1 soil based on total P. The plant height and leaf number increased in the plants grown in amended pots compared to control pot. The dry weight of shoots and roots in the control pot were 14.3 and 2.8 g, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
2
8
0
1
Order By: Relevance
“…1). A similar effect was observed in the study of, for example, van Dam and Ehlert (2008), Liu et al (2011), Meena et al (2007, Mohanty et al (2006), and Uddin et al (2012). These authors attributed this phenomenom to the fact that most of the P contained in TSP is water-soluble (96% in this study) and therefore partly captured by the substantial amount of Fe and Al oxides in acidic sandy soils (Feox = 34 mmol kg -1 , Alox = 66 mmol kg -1 in this study).…”
Section: Effect Of Bio-based Fertilizer On Biomass Yield and Phosphorsupporting
confidence: 65%
“…1). A similar effect was observed in the study of, for example, van Dam and Ehlert (2008), Liu et al (2011), Meena et al (2007, Mohanty et al (2006), and Uddin et al (2012). These authors attributed this phenomenom to the fact that most of the P contained in TSP is water-soluble (96% in this study) and therefore partly captured by the substantial amount of Fe and Al oxides in acidic sandy soils (Feox = 34 mmol kg -1 , Alox = 66 mmol kg -1 in this study).…”
Section: Effect Of Bio-based Fertilizer On Biomass Yield and Phosphorsupporting
confidence: 65%
“…However, the differences between the application rates of Elixir were not statistically significant. In agreement with [9], the application of Elixir had significantly (P = 0.001) affected the produced fresh weight, dry weight and number of leaves. Likewise, there were no significant differences between different application rates.…”
Section: Effect Of Elixir On Some Soil Properties and Plant Growth Pasupporting
confidence: 69%
“…Elixir being acidic and the high numbers of micro-organisms in it might have reduced the soil pH and improved the availablility of nutrients. Supporting increase in P amounts in plants under organic amendments was reported by Mejbah Uddin et al, (2012). …”
Section: Effect Of Elixir On Some Soil Properties and Plant Growth Pamentioning
confidence: 89%
See 1 more Smart Citation
“…Based on the experimental results carried out by [11] it can be concluded that bio-activators can accelerate the composting of livestock feces and lower C/N ratio. Findings by [12] revealed that phosphorus concentration in plant parts increased with organic amendments. In the last ten to fifteen years, the importance of micro-organisms in decomposition of organic residues, release of nutrients, availing of nutrients to the plants in available forms and conditioning of soils was recognized and started to be utilized [13].…”
Section: Introductionmentioning
confidence: 99%